1992
DOI: 10.1007/bf00031700
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for dispersal in annual and perennial grasses in a savanna in Botswana

Abstract: Dispersal of 11 dominant grass species in the savanna of southern Botswana was investigated. The dispersal is autochorous, anemochorous and epizoochorous independent of the life-cycle (annuals, perennials). Dispersal distances were estimated experimentally. Anemochorous species with a plume-like spikelet such as Chloris virgata and Enneapogon cenchroides have a low rate of descent ( < 1 m s 1) and a low Reynold number (100-110). Nevertheless they can only be transported up to 13 m from the originating infructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
5
28
1
Order By: Relevance
“…Tallgrass prairie and savanna habitats gradually re-established themselves in the northern USA between 9,000 and 5,000 ybp, not in a single event, but in multiple events over thousands of years (Clark et al 2001;Jacobson and Grimm 1986;Kelley et al 2006). As a sessile organism, switchgrass was entirely dependent on birds and mammals as agents to facilitate migration of seeds to new locations (Ernst et al 1992;Ocumpaugh et al 1996;Pakeman 2001;Webb 1986). This provided a mechanism for multiple introductions of switchgrass to new colonization sites, potentially originating from a diverse array of existing sites and populations.…”
Section: Geographic Distribution Of Ecotypes and Lineagesmentioning
confidence: 99%
“…Tallgrass prairie and savanna habitats gradually re-established themselves in the northern USA between 9,000 and 5,000 ybp, not in a single event, but in multiple events over thousands of years (Clark et al 2001;Jacobson and Grimm 1986;Kelley et al 2006). As a sessile organism, switchgrass was entirely dependent on birds and mammals as agents to facilitate migration of seeds to new locations (Ernst et al 1992;Ocumpaugh et al 1996;Pakeman 2001;Webb 1986). This provided a mechanism for multiple introductions of switchgrass to new colonization sites, potentially originating from a diverse array of existing sites and populations.…”
Section: Geographic Distribution Of Ecotypes and Lineagesmentioning
confidence: 99%
“…To compile our data set, we used six previous studies that summarized published dispersal information and addressed a large number of species (Willson 1993, Hughes et al 1994, Cain et al 1998, Bullock and Clarke 2000, Ness et al 2004, Vittoz and Engler 2007, as well as studies in which the dispersal distances were derived from models parameterized with field data (e.g., Sheldon and Burrows 1973, Augspurger 1986, Matlack 1987, Ernst et al 1992, Sto¨cklin and Ba¨umler 1996, Kiviniemi and Telenius 1998, Jongejans and Telenius 2001, Soons and Ozinga 2005. We additionally searched the ISI Web of Science for papers published up until 31 January 2012, using the keywords ''seed,'' ''dispersal,'' and ''distance.''…”
Section: Data On Seed Dispersal Distances and Plant Traitsmentioning
confidence: 99%
“…Additional information about seed and plant characteristics may help in explaining seed dispersal distances. Models of seed dispersal often incorporate information about seed mass and shape (e.g., Augspurger 1986, Matlack 1987, Ernst et al 1992. A recent global review of seed dispersal distances of over 300 species (Thomson et al 2011) revealed that plant height is more important than seed mass in determining seed dispersal distances.…”
Section: Introductionmentioning
confidence: 99%
“…Protected seeds may either be stimulated to germinate or remain dormant or quiescent (Baskin andBaskin 1989, Paula andPausas 2008). Seeds can avoid the effects of fire through a number of mechanisms including burial in the soil either by animals or with the aid of hygroscopic awns (Ernst et al 1992). Because grassland fires move quickly, soil temperatures may remain unchanged even in the upper layers, thereby sparing buried seeds from temperature extremes (Gillon 1983).…”
mentioning
confidence: 99%
“…Because grassland fires move quickly, soil temperatures may remain unchanged even in the upper layers, thereby sparing buried seeds from temperature extremes (Gillon 1983). In contrast, seeds resting on the soil surface can be completely destroyed by direct combustion or exposure to temperatures generated during fires (Ernst et al 1992).…”
mentioning
confidence: 99%